Winding Switching Simulation of Dual-Stator Permanent Magnet Synchronous Motor for Electric Vehicles - Yaling Wang; Yongjian Sun; Yueqin Dun; Guobin Chen; Qifan Yang; Xiaocui Zhang (International Conference on Advanced Mechatronic Systems, 2018)
The dual-stator permanent magnet synchronous motor (DSPMSM) has two sets independent windings due to its dual-stator structure. Then the windings can be connected in multiple modes, so that the motor can operate in various states by winding switching. In this paper., the winding switching method is studied., and the winding switching circuit using the triode AC switches (TRIAC) is proposed., which is verified by FEA simulation.